Plio-Pleistocene coupled benthic stable isotope and Mg/Ca measurements from Site 1209 in the Northwest Pacific - Friso Marc de Graaf; Heather L Ford; David J R Thornalley; Natalie J Burls; Rachel Mary Brown; Gavin L Foster; Chris M Brierley (PANGAEA, 2025)
Stable isotopes were measured on benthic foraminifera species Cibicidoides wuellerstorfi from ODP Site 1209 on the Shatsky Rise in the Northwest Pacific Ocean. Approximately 5 – 7 specimens were analysed at c. 4cm resolution along the core from 33 m - 58 m depth along the core for both oxygen and carbon isotopes using a VG ISOGAS SIRE dual inlet isotope ratio mass spectrometer at the Godwin Laboratory for Palaeoclimate Research at the University of Cambridge. For the section between 34 - 43 m depth along the core, Mg/Ca ratios were measured on the benthic foraminifera species Uvigerina peregrina. The samples underwent a modified reductive and oxidative cleaning process described in Boyle and Kegwin, 1982 and Barker et al., 2003 respectively, and were then analysed for trace metals by ICP-MS on a Thermo-Scientific Element 2 at the University of Southampton. The coupled stable isotopes and Mg/Ca measurements were converted to bottom-water temperature and seawater d18O values using the PSU Solver model of Thirumalai et al., 2017. Samples were put on an age model using a bayesian tie-point algorithm which matched oxygen isotope values to that of the ProbStack record of Ann et al., 2017.